Lessons learned: from dye-sensitized solar cells to all-solid-state hybrid devices. - Docampo, P; Guldin, S; Leijtens, T; Noel, N; Steiner, U; Snaith, H (2014)
The field of solution-processed photovoltaic cells is currently in its second spring. The dye-sensitized solar cell is a widely studied and longstanding candidate for future energy generation. Recently, inorganic absorber-based devices have reached new record efficiencies, with the benefits of all-solid-state devices. In this rapidly changing environment, this review sheds light on recent developments in all-solid-state solar cells in terms of electrode architecture, alternative sensitizers, and hole-transporting materials. These concepts are of general applicability to many next-generation device platforms.